Propionic acid enhances H2 production in purple phototrophic bacteria: insights into carbon and reducing equivalent allocation - Huang, Peitian (2025)
Biohydrogen is gaining popularity as a clean and cost-effective energy source. Among the various production methods, photo fermentation (PF) with purple phototrophic bacteria (PPB) has shown great opportunity due to its high hydrogen yield. In practice, this yield is influenced by several factors, with the carbon source, particularly simple organic acid, being a key element that has attracted considerable research interest. Short-chain volatile fatty acids (VFAs), such as acetate, propionate, and butyrate, are widely found in waste streams and dark fermentation (DF) effluent. However, most studies on these VFAs focus mainly on performance evaluation, with few exploring the underlying mechanisms, which limits their applicability in real-world scenarios. To uncover the metabolic mechanisms, this study uses metagenomics to clarify the processes of reducing power production and distribution during substrate assimilation. Meanwhile, this study presents the impact of short-chain VFAs on biohydrogen, polyhydroxyalkanoates (PHA) and glycogen production by PPB. The results show that: (1) over long-term cultivation at similar COD consumption rates of 0.06 g COD/d, PPB possessed the highest hydrogen yield when fed with propionate (0.620 L H2·g COD-1) compared with butyrate (0.434) and acetate (0.361); (2) with propionate as the substrate, PPB accumulated less PHA (7 % of dry biomass) but more glycogen content (11 %), compared to butyrate (15 % PHA and 8 % glycogen) and acetate (21 % PHA and 5 % glycogen); (3) metagenomic analysis revealed that propionate resulted in the highest amounts of reducing equivalents, followed by butyrate and acetate; hydrogen production was the most efficient pathway for utilizing the reducing power with propionate, as the CO2 fixation and PHA or glycogen synthesis were ineffective for electron dissipation. This study offers insights into metabolic mechanism that could guide waste stream selection and pretreatment processes to provide favorable VFAs for the PF process, thereby enhancing PPB biohydrogen production performance in practical applications.